2021
DOI: 10.1111/jocs.15524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation method of training simulation on biological models for cardiovascular surgery residents

Abstract: Objectives: The goal of this study was to describe and evaluate our simulation training program on biological models for the cardiovascular surgery residency program at our institution.Material and Methods: Since 2016, with the purpose to develop better practical performance and evaluate the improvement of resident's surgical skills, a simulation training program was implemented, composed of some elemental procedures in cardiovascular surgery. It was established with one wet lab session weekly lasting 2 h, coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Brandão and colleagues 26 described the results of a 5-week high-fidelity training program on AVR, MVR and coronary artery bypass surgery for second- and third-year cardiovascular surgery residents. After the simulation program, the residents received mean performance ratings on a 5-point Likert score of 4.79, 4.72, 4.47, 4.34 and 4.20 for anatomy knowledge, valve excision, stitches in the annulus, prosthesis implantation and time, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Brandão and colleagues 26 described the results of a 5-week high-fidelity training program on AVR, MVR and coronary artery bypass surgery for second- and third-year cardiovascular surgery residents. After the simulation program, the residents received mean performance ratings on a 5-point Likert score of 4.79, 4.72, 4.47, 4.34 and 4.20 for anatomy knowledge, valve excision, stitches in the annulus, prosthesis implantation and time, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement in surgical trainees’ time to completion of tasks, number of mistakes, skills scores and theoretical knowledge after participation in SBT has been reported. 5 , 11 , 12 , 26 28 , 30 , 35 37 The use of SBT in training for heart valve surgery is relatively limited compared to other surgical fields, such as coronary revascularization. 38 As such, further investigation into the use of SBT for teaching valve repair and replacement techniques is warranted to identify the optimal use of SBT for training surgical residents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These In general, most of the residents reported that the program could provide a realistic experience and be valuable in teaching surgical skills. 5 We observed that biological models with porcine or bovine hearts provided a high degree of realism. In the case of cardiac surgery, where surgical failure may result in patient morbidity and mortality, such a realistic simulation could reproduce better surgical results, which is essential before clinical application.…”
mentioning
confidence: 87%